Pengaruh Penggunaan Model Pembelajaran Paired Story Telling terhadap Keterampilan Menulis Karangan Narasi Siswa Kelas V MI Assa’Adah Bungah - Anita Firdaus; Afakhrul Masub Bakhtiar; Ismail Marzuki (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to determine the effect of the use of the Paired Story Telling learning model on the narrative essay writing skills of grade V students of MI Assa'Adah Bungah for the 2024/2025 Academic Year. The problems raised in this study focus on the low ability of students to write narrative essays in a sequential, interesting, and correct structure. The Paired Story Telling model was chosen because it is considered to increase students' interest and active involvement in learning to write by retelling the content of the story with their partners. The method used in this study is a pseudo-experiment with between subject design. The sample in this study consisted of two classes, namely the experimental class that was given treatment using the Paired Story Telling model, and the control class that was not given special treatment and still used conventional learning methods. The research instrument is in the form of a narrative essay writing test that has gone through a validity and reliability test. The population in this study is all students of class V MI Assa'Adah Bungah for the 2024/2025 Academic Year which totals 42 students. The data analysis technique used a t-test which showed that there was a significant difference between student learning outcomes in the experimental class and the control class. The results of the hypothesis test showed that the significance value was 0.000 < 0.05 which means that H₀ was rejected and Hₐ was accepted. Thus, it can be concluded that the use of the Paired Story Telling model has a significant effect on improving students' narrative essay writing skills. These findings suggest that collaborative learning models such as Paired Story Telling can be used as an alternative strategy in effective writing teaching in elementary schools.